STRATIGRAPHY OF THE TALITSA HORIZON (PALEOCENE) IN THE CENTRAL TRANS-URALS - Amon E.O.; Vasil'eva O.N.; Zhelezko V.I. (My University, 2003)
Data on a series of boreholes drilled in the central trans-Urals are used to characterize the Paleocene marine deposits of the Talitsa Horizon, which are widespread all over the trans-Urals and in West Siberia. Presented paleogeographic considerations are based on distribution on patterns of various fossils (foraminifers, radiolarians, dinocysts, and Selachii teeth) and on lithologic characteristics of their host deposits. Presented in addition are brief descriptions of underlying Maastrichtian (Gan'kino Formation) and overlying Thanetian (Serov Formation) deposits. The character and position of the Cretaceous-Paleogene boundary that is placed at the Talitsa Horizon base are described. Regional zonation of foraminifers and dinocysts is substantiated, and problems of regional and interregional correlations are briefly discussed.
Keywords: Paleocene; Cenozoic::Paleogene::Paleocene; Кайнозой::Палеоген::Палеоцен